ENVIRONMENTAL FACTORS AFFECTING FINANCIAL PERFORMANCE DURING THE COVID-19 PANDEMIC IN ASEAN: SOCIAL DISCLOSURE AS MODERATING - Rusli, Yohanes Mardinata; Pangestu, Juan Carlos (School of Accountancy, University of Agung Podomoro, 2022)
This study discusses the factors of environmental performance, environmental disclosure, andcorporate social disclosure that affect corporate financial performance. The current global warming isworrying enough that the country's leaders are committed to reducing the level of carbon emissions ineach country. Environmental disclosures and social disclosures that must exist during the COVID-19pandemic have not been implemented due to large-scale social restriction regulations from thegovernment, so they cannot be disclosed. The research subject is a mining company in one of thelargest ASEAN countries, namely Indonesia. Meanwhile, the object of this research is the Annual andSustainability report for the period 2018-2021 published on each ASEAN country's Stock Exchangeswebsite. The study results show that Environmental Disclosure significantly influences the FinancialPerformance of mining companies listed on the IDX in 2018-2020.